High-performance adhesive for automobile glass process protection

By using high-performance adhesives such as hyperbranched perfluoropolyether polyurethane acrylate oligomer in the automotive glass process, the problems of insufficient adhesive strength, high temperature resistance and glue removal performance of the adhesive are solved, and the problem of insufficient adhesive strength, high temperature resistance and glue removal performance are achieved. Efficient and environmentally friendly automotive glass protection effect.

CN119119945APending Publication Date: 2024-12-13ANHUI LIUMAI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411450247.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing adhesives used in automotive glass processes have insufficient adhesive strength, poor high temperature resistance, poor glue removal performance, and safety and environmental protection issues, which affect production efficiency and product qualification rate.

Method used

Using hyperbranched perfluoropolyether polyurethane acrylate oligomer, methylvinyl silicone rubber, isocyanoethyl methacrylate and other raw materials, the interpenetrating network structure is formed through photo-induced curing reaction, and combined with hydroxyethylhexahydrogen homo The triazine, 2,4,6-trivinylboroxane, N-vinyl caprolactam and other components form high-performance adhesives, avoid the use of volatile organic solvents, and achieve high adhesion, high temperature resistance and Quickly remove glue.

Benefits of technology

It significantly improves the adhesive strength, high temperature resistance and anti-gluing performance of the adhesive, reduces the energy consumption and VOC emissions of the production process, improves the production efficiency and finished product qualification rate, and is safe and environmentally friendly to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-performance adhesive for automobile glass process protection, and relates to the technical field of adhesives, and the high-performance adhesive is prepared from the following raw materials: hyperbranched perfluoropolyether urethane acrylate oligomer, methyl vinyl silicone rubber, isocyano ethyl methacrylate, hexahydro-1, 3, 5-tris (hydroxyethyl)-s-triazine, 2, 4, 5-trimethyl-1, 3-pentanediol monoisobutyrate, 2, 4, 5-trimethyl-1, 3-pentanediol monoisobutyrate, 2, 4, 5-trimethyl-1, 3-pentanediol The coating is prepared from the following raw materials: 2, 6-trivinyl boroxane, methyl vinyl di (diacetylketoxime) silane, N-vinyl caprolactam, 2-(1-propylene-2-yl) benzo [D] oxazole, 3, 3 '-diamino-4, 4'-difluorodiphenyl sulfone, 3-(1, 1-difluoro-2-propylene-1-yl)-2 (1H)-quinoxalinone, a diluent, a photoinitiator, a catalyst and a defoaming agent. The adhesive is high in adhesive strength, excellent in high temperature resistance, good in adhesive removing performance and safe and environment-friendly to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a high-performance adhesive used for protecting automobile glass during manufacturing. Background Art

[0002] With the development of economy and the progress of society, cars have become the main means of transportation for people. The automobile industry has also shown a prosperous development year by year. More and more automobile products are manufactured, and people have higher and higher requirements for their performance. Among the parts of the car, the on-board glass display screen is a relatively important component, and its output and efficiency need to be continuously improved. Improving efficiency and reducing pollution are urgent issues that the glass processing industry needs to solve.

[0003] In order to give the car glass display more functionality, it is usually necessary to do special treatment on the front, such as anti-scratch, anti-glare, anti-fingerprint, etc. In order to prevent light leakage from the edges, ink will be printed on the back. During the above process, in order to prevent the untreated part from being affected, it is necessary to protect the surface, so a large amount of protective adhesive is needed. Most of the existing adhesives used in the automotive glass process are solvent-based adhesives containing volatile organic solvents, which will affect the scraper performance, working environment, and curing time, and the process is complicated; this type of adhesive on the market also has more or less residual glue when peeled off, which needs to be wiped with solvents, and has poor high temperature resistance. High temperature will cause the protective adhesive to be unable to be debonded, reducing production efficiency and product qualification rate.

[0004] In order to solve the above problems, the Chinese invention patent with application publication number CN116083007A discloses a mobile phone glass process protective pressure-sensitive adhesive, and the raw materials for preparation include, by weight: 160-200 parts of propylene monomers, 180-250 parts of ethyl acetate, and 0.05-0.2 parts of initiators. The invention uses hydroxyethyl acrylamide to replace part of the hydroxyl-containing acrylate and isooctyl acrylate, and butyl acrylate undergoes copolymerization reaction, which effectively improves the distribution of hydroxyl groups in the polymer, and the polymer formed has a higher molecular weight and a higher hydroxyl content. The polymerization process is controllable, avoiding the occurrence of gelation during the polymerization reaction and reducing the proportion of small molecular weight copolymers. At the same time, the synergistic effect of aliphatic isocyanate curing agent and epoxy resin cross-linking agent is used to improve the cross-linking reaction activity, effectively improve the cross-linking density of the adhesive layer and the integrity of the cross-linking network, and inhibit the precipitation of oligomer components in the pressure-sensitive adhesive. However, the degumming time of the pressure-sensitive adhesive after high-temperature baking is still long, and the organic solvent ethyl acetate contained therein will affect the scraper performance, working environment, and curing time.

[0005] It can be seen that the development of a high-performance adhesive for automotive glass process protection that has high adhesive strength, excellent high temperature resistance, good debonding performance, and is safe and environmentally friendly meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the adhesive field. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a high-performance adhesive for automobile glass process protection that has high adhesive strength, excellent high temperature resistance, good debonding performance, and is safe and environmentally friendly.

[0007] The invention provides a high-performance adhesive for automobile glass process protection, which comprises the following raw materials in parts by weight: 30-40 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 8-12 parts of methyl vinyl silicone rubber, 5-8 parts of isocyanoethyl methacrylate, 1-3 parts of hydroxyethyl hexahydro-s-triazine, 2-4 parts of 2,4,6-trivinyl cycloboroxane, 1-3 parts of methyl vinyl di(butanone oxime) silane, 1-3 parts of N-vinyl caprolactam, 2-4 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1-2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.5-0.8 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 20-30 parts of diluent, 0.8-1 parts of photoinitiator, 0.2-0.4 parts of catalyst and 0.8-1.2 parts of defoaming agent.

[0008] Preferably, there is no special requirement for the source of the hyperbranched perfluoropolyether polyurethane acrylate oligomer. In one embodiment of the present invention, the hyperbranched perfluoropolyether polyurethane acrylate oligomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B.

[0009] Preferably, the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with a brand name of QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.

[0010] Preferably, the diluent is a mixture of ethyl acrylate, butyl acrylate and hydroxypropyl methacrylate in a mass ratio of 1:(0.8-1.2):(1-2).

[0011] Preferably, the photoinitiator is at least one of benzoin ethyl ether, benzoin isopropyl ether, diphenyl acetone, and 2,4-dihydroxybenzophenone.

[0012] Preferably, the catalyst is at least one of dibutyltin dilaurate DY-12 and organic bismuth DY-20.

[0013] Preferably, the defoaming agent is one or more of tributyl phosphate, defoaming agent Deqian 3100, and defoaming agent BYK088.

[0014] Another object of the present invention is to provide a method for preparing a high-performance adhesive for protecting automobile glass process, comprising the following steps: mixing the raw materials uniformly by weight, vacuuming and degassing for 1-2 hours, and finally standing and degassing before storing to obtain a high-performance adhesive for protecting automobile glass process.

[0015] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The method for preparing the high-performance adhesive for automobile glass process protection disclosed in the present invention only requires the raw materials to be mixed evenly and then degassed. No special equipment is required, and the energy consumption and labor intensity are low. The preparation efficiency and finished product qualification rate are high, and the method is suitable for industrial production and has a high value for promotion and application.

[0016] (2) The high-performance adhesive for automobile glass process protection disclosed in the present invention comprises the following raw materials in parts by weight: 30-40 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 8-12 parts of methyl vinyl silicone rubber, 5-8 parts of isocyanoethyl methacrylate, 1-3 parts of hydroxyethyl hexahydro-s-triazine, 2-4 parts of 2,4,6-trivinyl cycloboroxane, and 1-3 parts of methyl vinyl di(butanone oxime) silane. , 1-3 parts of N-vinyl caprolactam, 2-4 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1-2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.5-0.8 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 20-30 parts of diluent, 0.8-1 parts of photoinitiator, 0.2-0.4 parts of catalyst, 0.8-1.2 parts of defoamer. Through the mutual coordination and joint action of various raw materials, the prepared adhesive can be endowed with advantages such as high adhesive strength, excellent high temperature resistance, good degumming performance, safe and environmentally friendly use, etc.

[0017] (3) The high-performance adhesive for automobile glass protection disclosed in the present invention adopts UV curing method and does not add volatile organic solvents, which effectively solves the problems of high energy consumption and high VOC emissions of traditional heat-curing solvent-based products. By reasonably selecting the types and dosage ratios of various raw materials in the composition formula, the raw materials containing unsaturated olefin bonds can undergo copolymerization and curing reaction under the initiation of photoinitiator. At the same time, the isocyanate group on isocyanoethyl methacrylate can react chemically with other raw materials containing hydroxyl and / or amino groups to form an interpenetrating network structure, which effectively improves the bonding strength and high temperature resistance of the adhesive. During the high-temperature treatment process, its molecules will no longer continue to cross-link, and there will be no situation where debonding cannot occur, which greatly reduces the debonding time and improves the production efficiency and yield rate. Hyperbranched perfluoropolyether polyurethane, ester group, silicone rubber, triazine, cycloboroxane, oxime group, caprolactam, benzo[D]oxazole, difluorodiphenyl sulfone and fluoroquinoxalinone structures are simultaneously introduced into the formed film. These structures further improve the above-mentioned properties under the multiple effects of electronic effect, steric effect and conjugation effect. DETAILED DESCRIPTION

[0018] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1

[0019] A high-performance adhesive for protecting automobile glass in the manufacturing process is prepared from the following raw materials in parts by weight: 30 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 8 parts of methyl vinyl silicone rubber, 5 parts of isocyanoethyl methacrylate, 1 part of hydroxyethyl hexahydro-s-triazine, 2 parts of 2,4,6-trivinylcycloboroxane, 1 part of methylvinyl di(butanone oxime)silane, 1 part of N-vinyl caprolactam, 2 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1 part of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.5 part of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 20 parts of diluent, 0.8 part of photoinitiator, 0.2 part of catalyst and 0.8 part of defoamer.

[0020] The hyperbranched perfluoropolyether polyurethane acrylate polymer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B; the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with brand QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.; the diluent is ethyl acrylate, butyl acrylate, and hydroxypropyl methacrylate mixed in a mass ratio of 1:0.8:1; the photoinitiator is benzoin ethyl ether; the catalyst is dibutyltin dilaurate DY-12; and the defoaming agent is tributyl phosphate.

[0021] A method for preparing a high-performance adhesive for protecting automobile glass process comprises the following steps: mixing raw materials uniformly according to weight, vacuuming and degassing for 1 hour, and finally standing and degassing before storing to obtain the high-performance adhesive for protecting automobile glass process. Example 2

[0022] A high-performance adhesive for protecting automobile glass in the manufacturing process is prepared from the following raw materials in parts by weight: 33 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 9 parts of methyl vinyl silicone rubber, 6 parts of isocyanoethyl methacrylate, 1.5 parts of hydroxyethyl hexahydro-s-triazine, 2.5 parts of 2,4,6-trivinyl cycloboroxane, 1.5 parts of methyl vinyl di(butanone oxime) silane, 1.5 parts of N-vinyl caprolactam, 2.5 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1.2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.6 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 23 parts of diluent, 0.85 parts of photoinitiator, 0.25 parts of catalyst and 0.9 parts of defoamer.

[0023] The hyperbranched perfluoropolyether polyurethane acrylate polymer is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B; the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with brand QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.; the diluent is ethyl acrylate, butyl acrylate, and hydroxypropyl methacrylate mixed in a mass ratio of 1:0.9:1.2; the photoinitiator is benzoin isopropyl ether; the catalyst is organic bismuth DY-20; and the defoamer is defoamer Deqian 3100.

[0024] A method for preparing a high-performance adhesive for automobile glass process protection comprises the following steps: mixing raw materials uniformly according to weight, vacuuming and degassing for 1.2 hours, and finally standing and degassing before storing to obtain a high-performance adhesive for automobile glass process protection. Example 3

[0025] A high-performance adhesive for protecting automobile glass in the manufacturing process is prepared from the following raw materials in parts by weight: 35 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 10 parts of methyl vinyl silicone rubber, 6.5 parts of isocyanoethyl methacrylate, 2 parts of hydroxyethyl hexahydro-s-triazine, 3 parts of 2,4,6-trivinyl cycloboroxane, 2 parts of methyl vinyl di(butanone oxime) silane, 2 parts of N-vinyl caprolactam, 3 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1.5 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.65 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 25 parts of diluent, 0.9 parts of photoinitiator, 0.3 parts of catalyst and 1 part of defoamer.

[0026] The hyperbranched perfluoropolyether polyurethane acrylate polymer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B; the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with brand QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.; the diluent is ethyl acrylate, butyl acrylate, and hydroxypropyl methacrylate mixed in a mass ratio of 1:1:1.5; the photoinitiator is diphenyl acetone; the catalyst is dibutyltin dilaurate DY-12; and the defoamer is defoamer BYK088.

[0027] A method for preparing a high-performance adhesive for automobile glass process protection comprises the following steps: mixing raw materials uniformly according to weight, vacuuming and degassing for 1.5 hours, and finally standing and degassing before storing to obtain a high-performance adhesive for automobile glass process protection. Example 4

[0028] A high-performance adhesive for protecting automobile glass in the manufacturing process is prepared from the following raw materials in parts by weight: 38 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 11 parts of methyl vinyl silicone rubber, 7.5 parts of isocyanoethyl methacrylate, 2.5 parts of hydroxyethyl hexahydro-s-triazine, 3.5 parts of 2,4,6-trivinyl cycloboroxane, 2.5 parts of methyl vinyl di(butanone oxime) silane, 2.5 parts of N-vinyl caprolactam, 3.5 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1.8 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.75 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 28 parts of diluent, 0.95 parts of photoinitiator, 0.35 parts of catalyst and 1.1 parts of defoamer.

[0029] The hyperbranched perfluoropolyether polyurethane acrylate polymer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B; the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with brand QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.; the diluent is ethyl acrylate, butyl acrylate, and hydroxypropyl methacrylate mixed in a mass ratio of 1:1.2:2; the photoinitiator is benzoin ethyl ether, benzoin isopropyl ether, diphenyl acetone, and 2,4-dihydroxybenzophenone mixed in a mass ratio of 1:2:3:1; the catalyst is dibutyltin dilaurate DY-12 and organic bismuth DY-20 mixed in a mass ratio of 3:5; the defoamer is tributyl phosphate, defoamer Deqian 3100, and defoamer BYK088 mixed in a mass ratio of 1:2:3.

[0030] A method for preparing a high-performance adhesive for automobile glass process protection comprises the following steps: mixing raw materials uniformly according to weight, vacuuming and degassing for 1.8 hours, and finally standing and degassing before storing to obtain a high-performance adhesive for automobile glass process protection. Example 5

[0031] A high-performance adhesive for protecting automobile glass in the manufacturing process is prepared from the following raw materials in parts by weight: 40 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 12 parts of methyl vinyl silicone rubber, 8 parts of isocyanoethyl methacrylate, 3 parts of hydroxyethyl hexahydro-s-triazine, 4 parts of 2,4,6-trivinyl cycloboroxane, 3 parts of methyl vinyl di(butanone oxime) silane, 3 parts of N-vinyl caprolactam, 4 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.8 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 30 parts of diluent, 1 part of photoinitiator, 0.4 parts of catalyst and 1.2 parts of defoamer.

[0032] The hyperbranched perfluoropolyether polyurethane acrylate polymer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105482680B; the methyl vinyl silicone rubber is selected from methyl vinyl silicone rubber with brand QLS-110-2, which is provided by Wuxi Quanli Technology Co., Ltd.; the diluent is ethyl acrylate, butyl acrylate, and hydroxypropyl methacrylate mixed in a mass ratio of 1:1.2:2; the photoinitiator is 2,4-dihydroxybenzophenone; the catalyst is dibutyltin dilaurate DY-12; and the defoamer is defoamer BYK088.

[0033] A method for preparing a high-performance adhesive for protecting automobile glass process comprises the following steps: mixing raw materials uniformly according to weight, vacuuming and degassing for 2 hours, and finally standing and degassing before storing to obtain the high-performance adhesive for protecting automobile glass process.

[0034] Comparative Example 1 A high-performance adhesive for automobile glass process protection and a preparation method thereof, which is basically the same as Example 1, except that 2-(1-propylene-2-yl)benzo[D]oxazole and 3,3'-diamino-4,4'-difluorodiphenyl sulfone are not added, and an equal amount of hyperbranched perfluoropolyether polyurethane acrylate polymer is used instead of methyl vinyl silicone rubber.

[0035] Comparative Example 2 A high-performance adhesive for automobile glass process protection and a preparation method thereof, which is basically the same as Example 1, except that N-vinyl caprolactam and 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone are not added, and an equal amount of methyl vinyl silicone rubber is used instead of hyperbranched perfluoropolyether polyurethane acrylate polymer.

[0036] In order to further illustrate the beneficial technical effects of the high-performance adhesive for automobile glass process protection involved in each embodiment of the present invention, relevant performance tests were conducted on the high-performance adhesive for automobile glass process protection involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: (1) Adhesion test: The adhesive obtained in each example was coated on a mirror stainless steel plate (the stainless steel plate was first wiped clean with anhydrous alcohol and dried), and the dry coating thickness was 25 μm; then dried at 80°C for 2 min, cured under ultraviolet light with a wavelength of 250 nm for 30 min, and then aged at 40°C for 3 days; the adhesion was tested using a tensile tester, with a peeling angle of 180° and a peeling speed of 300 mm / min.

[0037] (2) High temperature resistance test: The adhesive obtained in each example was applied to the car display glass, then dried at 80°C for 2 min, cured under ultraviolet light with a wavelength of 250 nm for 30 min, then aged at 40°C for 3 days, and finally baked at 200°C for 1 h. After cooling, the glass surface was observed under strong light in a dark and dust-free environment to see if there was any residue.

[0038] (3) Debonding time: The adhesive obtained in each example was coated on the car display glass, then dried at 80°C for 2 min, cured under ultraviolet light with a wavelength of 250 nm for 30 min, then aged at 40°C for 3 days, and finally baked at 250°C for 1 h. The debonding time was observed and calculated.

[0039] Table 1

[0040] As can be seen from Table 1, the high-performance adhesives for automobile glass process protection disclosed in the embodiments of the present invention have higher adhesion, better high temperature resistance and debonding performance than the comparative example products; the combined use of 2-(1-propylene-2-yl)benzo[D]oxazole, 3,3'-diamino-4,4'-difluorodiphenyl sulfone, N-vinyl caprolactam, 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, hyperbranched perfluoropolyether polyurethane acrylate polymer and methyl vinyl silicone rubber is beneficial to improving the above properties.

[0041] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A high-performance adhesive for automobile glass process protection, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of hyperbranched perfluoropolyether polyurethane acrylate oligomer, 8-12 parts of methyl vinyl silicone rubber, 5-8 parts of isocyanoethyl methacrylate, 1-3 parts of hydroxyethyl hexahydro-s-triazine, 2-4 parts of 2,4,6-trivinyl cycloboroxane, 1-3 parts of methyl vinyl di(butanone oxime) silane, 1-3 parts of N-vinyl caprolactam, 2-4 parts of 2-(1-propylene-2-yl)benzo[D]oxazole, 1-2 parts of 3,3'-diamino-4,4'-difluorodiphenyl sulfone, 0.5-0.8 parts of 3-(1,1-difluoro-2-propylene-1-yl)-2(1H)-quinoxalinone, 20-30 parts of diluent, 0.8-1 parts of photoinitiator, 0.2-0.4 parts of catalyst and 0.8-1.2 parts of defoamer.

2. The high-performance adhesive for automobile glass process protection according to claim 1, characterized in that: The methyl vinyl silicone rubber is selected from the methyl vinyl silicone rubber with the brand name of QLS-110-2.

3. The high-performance adhesive for automobile glass process protection according to claim 1, characterized in that: The diluent is a mixture of ethyl acrylate, butyl acrylate and hydroxypropyl methacrylate in a mass ratio of 1:(0.8-1.2):(1-2).

4. The high-performance adhesive for automobile glass process protection according to claim 1, characterized in that: The photoinitiator is at least one of benzoin ethyl ether, benzoin isopropyl ether, diphenyl acetone, and 2,4-dihydroxybenzophenone.

5. The high-performance adhesive for automobile glass process protection according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate DY-12 and organic bismuth DY-20.

6. The high-performance adhesive for automobile glass process protection according to claim 1, characterized in that: The defoaming agent is one or more of tributyl phosphate, defoaming agent Deqian 3100, and defoaming agent BYK088.

7. A method for preparing a high-performance adhesive for automobile glass process protection according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing the raw materials according to weight, vacuuming and degassing for 1-2 hours, and finally standing and degassing before storing to obtain a high-performance adhesive for protecting automobile glass process.

Citation Information

Patent Citations

  • UV-cured hyperbranched perfluoropolyether polyurethane acrylate coatings

    CN105482680B

  • Protective pressure-sensitive adhesive for mobile phone glass manufacturing process and preparation method of protective pressure-sensitive adhesive

    CN116083007A

  • Curable resin composition and cured product

    CN112585181A

  • Adhesive for polaroid and preparation method thereof

    CN116396714A

  • OCA optical adhesive with high ink segment difference filling capacity, adhesive tape and preparation method of OCA optical adhesive

    CN117050713A

Cited By

  • Sealant for aging-resistant cable joint and preparation method thereof

    CN119709107A

  • Aging-resistant sealing glue for cable joint and preparation method thereof

    CN119709107B